Politics of Dynasty in the Perspective of Islam: (A Theological and Ethical Study) - Aditoni, Agus (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Dynastic politics refers to a system of governance in which power is passed down through hereditary succession within a particular family or lineage. This phenomenon has occurred throughout the history of Islamic governance. This article aims to analyze dynastic politics from an Islamic perspective, both theologically and ethically, focusing on how this system is either accepted or opposed by Islamic teachings that emphasize the principles of justice, trustworthiness (amanah), and competence in the selection of leaders. The central question raised in this article is whether dynastic politics aligns with Islamic teachings, given Islam’s core principles in leadership selection, which prioritize capability, justice, and integrity.The data for this study were obtained through a literature review of classical and contemporary texts, including the Qur’an, hadiths, and works of Islamic scholars and political thinkers. The analysis uses a qualitative approach to explore theological and ethical arguments related to dynastic politics and compares them with the principles of leadership in Islam.The findings of this study indicate that although Islam does not explicitly prohibit dynastic politics, there are strong theological and ethical arguments asserting that leaders should be chosen based on competence and integrity, rather than lineage alone. As a concept, the article suggests that while dynastic systems have historical roots in Islamic political history, they should be critically re-evaluated in the modern context to align with the Islamic principles of social justice, community participation, and governmental accountability.